Groundwater Exploration for Water Well Sites in Abata Asunkere Community, Ilorin, Nigeria. - SULEMAN Kamaldeen Olasunkanmi (Zibeline Publisher, 2023)
In this study, Electrical resistivity investigation was carried out at different sections of Abata Asunkere Community, Ilorin, Nigeria with the aim of evaluating groundwater potential and properties of the aquifers. Geophysical technique adopted in this work were the Vertical Electrical Sounding (VES) and 2-D Electrical Resistivity Tomography (ERT) using Schlumberger array configuration. ERT was established on two profiles at the study area with total distance of 80 m apart with 5 m electrode spacing. Eight (8) VES points were sounded along the established profiles. The results revealed four geo-electric layers which correspond to the topsoil, clayey layer, sandy clay and the last layer to the bedrock in all the VES points sounded. The topsoil has apparent resistivity values ranging from 5 to 437 Ω-m and 0.5 m to 1.7 m while the last layer which is the fractured/fresh basement rock has resistivity ranges of 27 Ω-m to 9800 Ω-m and is characterized by infinite thickness. The curve types obtained are H, QH and HK curve type signatures with the H curve type covering about 60 % of the study area. High potential for groundwater was observed at the northeastern and southern part of the study area. Aquifers in most part of the study areas are relatively shielded from contamination because of high protective capacity of the overburden material. It was hence concluded that, the study area has a promising groundwater potential. Based on these results, groundwater exploration at optimum yield was recommended. Depending on the volume of water available during drilling, the maximum depth of drilling may reach up to 60 m.
Keywords: Groundwater; Survey; drilling; profile; Psuedo-section; Geosections.